1997
DOI: 10.1016/s0020-7292(97)00195-1
|View full text |Cite
|
Sign up to set email alerts
|

National audit on the practice and training in breech deliveries in the United Kingdom

Abstract: There is a high rate of cesarean section in breech presentation due to inadequate training of junior staff in vaginal breech delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This contrast can reflect the leadership of the regional university hospital, where practitioners of peripheral maternity clinics have often been trained. This variability in delivery practices is often reported between countries, maternity units and even obstetricians (25,(28)(29)(30). In a French survey of management for breech presentations in university hospitals, Michel et al found mean of 73.8% (range 50.3% to 98.3%) declared rates of caesarean section deliveries (28).…”
Section: Discussionmentioning
confidence: 99%
“…This contrast can reflect the leadership of the regional university hospital, where practitioners of peripheral maternity clinics have often been trained. This variability in delivery practices is often reported between countries, maternity units and even obstetricians (25,(28)(29)(30). In a French survey of management for breech presentations in university hospitals, Michel et al found mean of 73.8% (range 50.3% to 98.3%) declared rates of caesarean section deliveries (28).…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Among the family planning seekers, the majority of women opted for IUCDs or permanent tubal sterilization which continues to be popular in India. [11][12][13][14] CONCLUSION The present study highlights the fact that though awareness about contraceptive methods was high, the use of contraceptive methods was very low. This is the main reason for a high fertility rate.…”
Section: Resultsmentioning
confidence: 85%
“…It is reasonable to assume that the presence or absence of an obstetrician would have greater impact for vaginal than for cesarean breech birth. After all, learning how to do a cesarean section is a lot easier than learning how to conduct a vaginal breech birth, and there are also many more cesareans than there are breech births for acquiring the necessary know‐how (7,8). Yet, the overwhelming majority of births that were not attended by an obstetrician occurred in the planned vaginal group (126 of 144; 87.5%).…”
Section: The Care Differential: Route Of Delivery or Birth Attendant?mentioning
confidence: 99%